Identification of Small Peptides that Inhibit NADPH Oxidase (Nox2) Activation - Aron B. Fisher; Chandra Dodia; Sheldon I. Feinstein (MDPI AG, 2018)
Nicotinamide adenine phosphate (NADPH) oxidase type 2 (Nox2), a major source of reactive oxygen species in lungs, plays an important role in tissue damage associated with acute inflammatory diseases. The phospholipase A2 (PLA2) activity of peroxiredoxin 6 (Prdx6), called aiPLA2, is required for Nox2 activation through its role in the cellular generation of Rac, a key cytosolic component of the activation cascade. Lung surfactant protein A (SP-A) binds to Prdx6, inhibits its aiPLA2 activity, and prevents activation of Nox2. Based on protein docking software, we previously identified a 16 amino acid (aa) peptide derived from rat SP-A as the Prdx6 binding motif. We now identify the minimal effective sequences of rat/mouse and human SP-A as 9-aa sequences that we have called PLA2-inhibitory peptide (PIP).These sequences are PIP-1, rat/mouse; PIP-2, human; and PIP-3, a hybrid of PIPs 1&2. aiPLA2 activity in vitro was inhibited by 50% with ~7⁻10 µg PIP/µg Prdx6. Inhibition of the aiPLA2 activity and Nox2 activation of lungs in vivo was similar for intratracheal (IT) and intravenous (IV) administration of PIP-2, but required its incorporation into liposomes as a delivery vehicle; tissue ½ time for decrease of the in vivo inhibition of aiPLA2 activity after PIP-2 administration was ~50 h. These properties suggest that PIP-2 could be an effective therapeutic agent to prevent tissue injury associated with lung inflammation.